Dissecting the Satellite DNA Landscape in Three Cactophilic Drosophila Sequenced Genomes - de Lima, Leonardo G. (G3 (Bethesda), 2017)
Eukaryote genomes are replete with repetitive DNAs. This class includes tandemly repeated satellite DNAs (satDNA) which are among the most abundant, fast evolving (yet poorly studied) genomic components. Here, we used high-throughput sequencing data from three cactophilic Drosophila species, D. buzzatii, D. seriema, and D. mojavensis, to access and study their whole satDNA landscape. In total, the RepeatExplorer software identified five satDNAs, three previously described (pBuM, DBC-150 and CDSTR198) and two novel ones (CDSTR138 and CDSTR130). Only pBuM is shared among all three species. The satDNA repeat length falls within only two classes, between 130 and 200 bp or between 340 and 390 bp. FISH on metaphase and polytene chromosomes revealed the presence of satDNA arrays in at least one of the following genomic compartments: centromeric, telomeric, subtelomeric, or dispersed along euchromatin. The chromosomal distribution ranges from a single chromosome to almost all chromosomes of the complement. Fiber-FISH and sequence analysis of contigs revealed interspersion between pBuM and CDSTR130 in the microchromosomes of D. mojavensis. Phylogenetic analyses showed that the pBuM satDNA underwent concerted evolution at both interspecific and intraspecific levels. Based on RNA-seq data, we found transcription activity for pBuM (in D. mojavensis) and CDSTR198 (in D. buzzatii) in all five analyzed developmental stages, most notably in pupae and adult males. Our data revealed that cactophilic Drosophila present the lowest amount of satDNAs (1.9–2.9%) within the Drosophila genus reported so far. We discuss how our findings on the satDNA location, abundance, organization, and transcription activity may be related to functional aspects.